2023
DOI: 10.1017/s1049023x23005800
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality in Patients Transferred by Emergency Medical Services: Prospective Cohort Study

Abstract: Objective: This study aimed to determine the long-term mortality (one-year follow-up) associated with patients transferred by Emergency Medical Services (EMS), and to reveal the determinants (causes and risk factors). Methods: This was a multicenter, prospective, observational, controlled, ambulance-based study of adult patients transferred by ambulance to emergency departments (EDs) from October 2019 through July 2021 for any cause. A total of six Advanced Life Support (ALS) units, 38 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…6 This has also been reported, as for respiratory rate and age, for long-term mortality when dealing with all patients and not with disease-specific analysis. 24 Enriquez de Salamanca Gambara et al 24 also found that GCS and SpO2 were associated with mortality. Perhaps GCS was more related to neurological diseases than cardiovascular diseases, which is our case.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…6 This has also been reported, as for respiratory rate and age, for long-term mortality when dealing with all patients and not with disease-specific analysis. 24 Enriquez de Salamanca Gambara et al 24 also found that GCS and SpO2 were associated with mortality. Perhaps GCS was more related to neurological diseases than cardiovascular diseases, which is our case.…”
Section: Discussionmentioning
confidence: 93%
“…23 The Open access long-term mortality relationship with age has already been described in the prehospital setting. 24 Lactate was statistically related to long-term mortality. The lactate value as a predictor of mortality is well documented in prehospital critical care and represents a very powerful indicator of mitochondrial hypoperfusion, directly affecting the production of bioavailable energy for all physiological processes, including the cardiovascular system.…”
Section: Discussionmentioning
confidence: 94%